Creative cash flow reporting : uncovering sustainable financial performance - Mulford, Charles W., 1951- (J. Wiley, 2005)
Successful methodology for identifying earnings-related reporting indiscretionsCreative Cash Flow Reporting and Analysis capitalizes on current concerns with misleading financial reporting on misleading financial reporting. It identifies the common steps used to yield misleading cash flow amounts, demonstrates how to adjust the cash flow statement for more effective analysis, and how to use adjusted operating cash flow to uncover earnings that have been misreported using aggressive or fraudulent accounting practices.